Gene Promoter Methylation Patterns throughout the Process of Cervical Carcinogenesis - Nan Yang; Esther R. Nijhuis; Haukeline H. Volders; Jasper J. H. Eijsink; Ágnes Lendvai; Bo Zhang; Harry Hollema; Ed Schuuring; G. Bea A. Wisman; Ate G. J. van der Zeea (Cellular Oncology)
Objectives: To determine methylation status of nine genes, previously described to be frequently methylated in cervical cancer, in squamous intraepithelial lesions (SIL).